Exploiting Users' Personal and Public Information for Personal Photo Annotation - Sarin, S.; Nagahashi, T.; Miyosawa, T.; Kameyama, W. (2007 IEEE International Conference on Multimedia and Expo, 2007)
Annotation is the core item to enable efficient access to media. Thus, automatic annotation is a highly challenging problem. We present a novel solution to personal digital photograph annotation problem which annotates photo based on users' personal, and public information. We use timestamps of photo together with exact location name as pivots to search for more contextual metadata from users' emails, schedules, web browsing histories and public information repositories such as online encyclopedia and news Web sites. A notable contribution of our approach is that it can effectively leverage the background information of users' daily activities and their ambient environment to semi-automatically annotate their photographs. Experimental results conducted with 10 subjects and a total of 313 photos show that we can reduce 33% of annotation time over manual annotation and we also obtain very encouraging accuracy results.